Noise reduction with 3D printed acoustic metamaterial - Wong, Yi Kuan (Nanyang Technological University, 2021)
Harmful effects of noise pollution on people’s mental and physical health have been on the rise in densely populated cities such as Singapore and Hong Kong. This noise pollution commonly originates from vehicular and traffic noises and construction. This is particularly prevalent in tropical cities where houses tend to have casement windows which is opened to provide ventilation for people’s homes and closed to prevent external noise pollution from entering their homes. However, there has not been a commercially viable method where both ventilation and noise attenuation can be achieved. With this in mind, the Noise Reducing Ventilation Unit (NRVU) is conceived. By making use of 3D printed metamaterials to harness the Helmholtz Resonance Principle, the NRVU is cost-effective product that provides ventilation with noise reduction capability. The Helmholtz Resonance Principle works by assigning a negative effective bulk modulus to air, which creates an evanescent wave. This wave does not propagate thus sound waves cannot propagate through the NRVU, resulting in sound attenuation. The NRVU will be made up of an array of cells that can be tessellated such as triangles, squares and hexagons. Each cell will then be assigned with different resonant frequencies to provide a low frequency broadband noise attenuation effect. Experiments and simulations were first done using a hexagonal NRVU cell with 4-mm and 6-mm diameter holes. Subsequently, square and triangular NRVU of 6mm diameter holes were used. The results showed that hexagonal, square and triangle NRVU cells with 6mm holes were capable of achieving sound attenuation levels 6%, 4% and 7% of source output in RMS Voltage.